2020
DOI: 10.1007/jhep05(2020)085
|View full text |Cite
|
Sign up to set email alerts
|

Higher harmonic non-linear flow modes of charged hadrons in Pb-Pb collisions at $$ \sqrt{s_{\mathrm{NN}}} $$ = 5.02 TeV

Abstract: Anisotropic flow coefficients, v n , non-linear flow mode coefficients, χ n,mk , and correlations among different symmetry planes, ρ n,mk are measured in Pb-Pb collisions at √ s NN = 5.02 TeV. Results obtained with multi-particle correlations are reported for the transverse momentum interval 0.2 < p T < 5.0 GeV/c within the pseudorapidity interval 0.4 < |η| < 0.8 as a function of collision centrality. The v n coefficients and χ n,mk and ρ n,mk are presented up to the ninth and seventh harmonic order, respectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 120 publications
(146 reference statements)
1
22
0
Order By: Relevance
“…The most important remaining open questions in the field are the location of the critical point (T c ) in the QCD phase diagram and temperature dependence of specific shear (η) and bulk (ζ) viscosity of the QGP. The flow analysis in LHC has been very successful and provides valuable information to the field [2][3][4][5][6]. For example, the main constraints for the QGP properties using the Bayesian analysis [7] in the theory came from the AL-ICE measurements [2,8,9] with both low and high beam energy data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important remaining open questions in the field are the location of the critical point (T c ) in the QCD phase diagram and temperature dependence of specific shear (η) and bulk (ζ) viscosity of the QGP. The flow analysis in LHC has been very successful and provides valuable information to the field [2][3][4][5][6]. For example, the main constraints for the QGP properties using the Bayesian analysis [7] in the theory came from the AL-ICE measurements [2,8,9] with both low and high beam energy data.…”
Section: Introductionmentioning
confidence: 99%
“…There had been new observables that give much stronger constraints to the theory [3,4], where they show good sensitivities especially to η/s(T) and ζ/s(T). The correlation strength measured in [3,4] was experimentally decomposed into two components as linear and non-linear flow mode in [5,17] for the first time in the field, which gives a better understanding of our harmonic analysis and its origin both with LHC Run 1 (2009-2013) and Run 2 (2015-2018) data.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the initial energy-density profile within the overlap region are thought to be the origin of the triangular flow, v 3 [8][9][10]. Higher order harmonics are strongly damped, do not depend linearly on the initial JHEP10(2020)141 anisotropy, and have significant contributions from the interplay of lower order harmonics [11][12][13][14][15]. The ALICE Collaboration published extensive studies of anisotropic flow measurements for identified light and strange particles [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these observations are collective effects, which are related to the formation of a strongly interacting quark-gluon plasma (QGP), which exhibits hydrodynamic behavior (see the reviews [8][9][10]). Recent theoretical [11][12][13] and experimental [14][15][16][17] advancements have contributed significantly to the understanding of the transport properties of the QGP. Similar long-range correlations are also observed in high-multiplicity proton-proton (pp) [18][19][20][21], proton-nucleus (pA) [22][23][24][25], and light nucleus-nucleus collisions [26,27].…”
Section: Introductionmentioning
confidence: 99%